Simultaneous Measurement of Muon Neutrino νμ Charged-Current Single π⁺ Production in CH, C, H₂ O, Fe, and Pb Targets in MINERvA - Bercellie, A.; Kroma-Wiley, K.A.; Akhter, S.; Ahmad Dar, Z.; Akbar, F.; Ansari, V.; Ascencio-Sosa, M.V.; Athar, M.; Bellantoni, L.; Betancourt, M.; Bodek, A.; Bonilla, J.L.; et al. (American Physical Society, 2023)
Neutrino-induced charged-current single π⁺ production in the Δ(1232) resonance region is of considerable interest to accelerator-based neutrino oscillation experiments. In this Letter, high statistic differential cross sections are reported for the semiexclusive reaction νµA → μ⁻π⁺+ nucleon(s) on scintillator, carbon, water, iron, and lead targets recorded by MINERvA using a wideband νμ beam with ⟨Eᵥ⟩≈6 GeV. Suppression of the cross section at low Q² and enhancement of low Tπ are observed in both light and heavy nuclear targets compared with phenomenological models used in current neutrino interaction generators. The cross sections per nucleon for iron and lead compared with CH across the kinematic variables probed are 0.8 and 0.5 respectively, a scaling which is also not predicted by current generators.
Keywords: Physics; Charged current; Neutrino; Muon; Nuclear physics; Nucleon; Particle physics; Muon neutrino; Neutrino oscillation; Lepton; Current (fluid); Production (economics); Oscillation (cell signaling); Coupling (piping); Neutral current; Neutrino detector; Electron; Chemistry; https://purl.org/pe-repo/ocde/ford#1.03.03